p53 mutation regulates PKD genes and results in co-occurrence of PKD and tumorigenesis - Haili Li; Yongjin Zhang; Juhua Dan; Ruoyu Zhou; Cui Li; Rong Li; Xiaoming Wu; Sanjay Kumar Singh; Jeffrey T. Chang; Julun Yang; Ying Luo (Cancer Biology & Medicine, 2019)
Objective Polycystic kidney disease (PKD) is the major cause of kidney failure and mortality in humans. It has always been suspected that the development of cystic kidney disease shares features with tumorigenesis, although the evidence is unclear. Methods We crossed p53 mutant mice (p53N236S, p53S) with Werner syndrome mice and analyzed the pathological phenotypes. The RNA-seq, ssGSEA analysis, and real-time PCR were performed to dissect the gene signatures involved in the development of disease phenotypes.Results We found enlarged kidneys with fluid-filled cysts in offspring mice with a genotype of G3mTerc-/-WRN-/-p53S/S (G3TM). Pathology analysis confirmed the occurrence of PKD, and it was highly correlated with the incidence of tumorigenesis. RNA-seq data revealed the gene signatures involved in PKD development, and demonstrated that PKD and tumorigenesis shared common pathways, including complement pathways, lipid metabolism, mitochondria energy homeostasis and others. Interestingly, this G3TM PKD and the classical PKD1/2 deficient PKD shared common pathways, possibly because the mutant p53S could regulate the expression levels of PKD1/2, Pkhd1, and Hnf1b.Conclusions We established a dual mouse model for PKD and tumorigenesis derived from abnormal cellular proliferation and telomere dysfunction. The innovative point of our study is to report PKD occurring in conjunction with tumorigenesis. The gene signatures revealed might shed new light on the pathogenesis of PKD, and provide new molecular biomarkers for clinical diagnosis and prognosis.